الاستغراق الوظيفي وعلاقته بمستوي الاحتراق الوظيفي لدي العاملين بشركات السياحة المصرية - Said Imam, Mahmoud (Finance and Business Economies Review, 2018)
Job Involvement is one of the important methods to improve Employees Performance level within travel agencies, as well as reduce the level of Job Burnout. The study aimed to identify the impact of Job Involvement on Job Burnout of employees in The Egyptian Travel Agencies Category A. To achieve the objective of the study, 405 Questionnaires were distributed to a random sample of employees in travel agencies Category A, while 370 forms were valid for statistical analysis. The study found that Job Involvement leads to decrease the level of Job Burnout of employees in The Egyptian Travel Agencies Category A. Keywords: Job Involvement, Emotional Involvement, Cognitive Involvement, Behavioral Involvement, Job Burnout, Travel Agencies.